Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

[ 36 + ( 3 × 2 ) ] ÷ 6

Sagot :

Answer:

7

Step-by-step explanation:

[36 + ( 3 × 2 ) ] ÷ 6 = 7

Answer:

7

Step-by-step explanation:

[ 36 + ( 3 × 2 ) ] ÷ 6

= [ 36 + 6 ] ÷ 6

= [ 42 ] ÷ 6

= 7